Mahasiswa Cerdas Tangkal Berita Hoaks di Era Disrupsi melalui Literasi Digital - Aisyah, Nagita Histimuna (Lembaga Yasin AlSys, 2021)
The student body is one of the most important assets in a nation, especially in an era where information is disseminated very easily and quickly through the internet or digital media. But unfortunately, that ease has brought not only positive but also negative effects, such as the hoax easily spread especially when it is not accompanied by an understanding of digital literacy. It is a challenge that will then require students not only to grow with the times, but it must be wise not to become one knowingly or unknowingly spreading the hoax. In conclusion, in the use of social media, critical behavior becomes one of the principal things to prevent unnecessary communication from reading information and its origins. Hence in this post, the author mentions some things or attitudes that students can do to be clever and wise in digital media to counter the spread of hoaxes that are so dangerous to the nation, based on digital literacy.